The Impact of Fintech Innovations on Traditional Banking Practices and Customer Preferences in Nepal - Nepal, Aayush (Nepalese Journal of Finance, 2025)
This study examines the impact of the impact of fintech innovations on traditional banking practices and customer preferences in Nepal. Customer adoption and customer preference are the dependent variables. The selected independent variables are brand image, perceived risk, perceived ease of use (PEOU), social influences, consumer satisfaction, and accessibility and convenience. The primary source of data is used to assess the opinions of the respondents regarding these variables in the context of fintech in Nepal. The study is based on primary data with 188 respondents. To achieve the purpose of the study, a structured questionnaire is prepared. Descriptive statistics, Kendall’s Tau correlations, and regression models are estimated to test the significance and importance of f intech adoption and its impact on traditional banking practices and customer preferences in Nepal. The study showed that brand image has a positive impact on customer preference and adoption of fintech platforms. It implies that an enhanced brand image leads to increased customer preference and adoption. The result also showed that perceived risk has a positive impact on customer preference and adoption of fintech platforms. It implies that higher perceived risk leads to increased customer preference and adoption. Moreover, perceived ease of use (PEOU) has a positive impact on customer preference and adoption of fintech platforms. It implies that greater perceived ease of use leads to increased customer preference and adoption. Furthermore, social influences have a positive impact on customer preference and adoption of fintech platforms indicating that stronger social influence leads to increased customer preference and adoption. Similarly, the result also showed that consumer satisfaction has a positive impact on customer preference and adoption of fintech platforms. It indicates that increased consumer satisfaction leads to increased customer preference and adoption. The result also showed that accessibility and convenience have a positive impact on customer preference and adoption of fintech platforms. It implies that improved accessibility and convenience lead to increased customer preference and adoption.